Cervicogenic headache, incidence and differential diagnosis - Souza, Cristiano de Bem Torquato de; Ferreira, Pablo Guarisco; Botelho, Wesley Gabriel Novaes; Pereira, Kleber Fernando; César, Alcântara Ramos de Assis (Headache Medicine, 2023)
Full abstract in PDF.